Analisis Kekuatan Material Mata Potong pada Mesin Pemipil Jagung Multifungsi - Firdaus, Muhammad; Fernanda, Yolli (Lembaga Yasin AlSys, 2025)
This study aims to evaluate the effect of heat treatment on the hardness of ST 37 steel, analyze the structural strength of a cutting blade using Finite Element Analysis (FEA) on AISI 1045 material, and test the functional performance of a corn sheller machine under varying rotational speeds. Vickers hardness testing (ASTM E18) revealed that tempering at 250°C for one hour increased the hardness of ST 37 steel from 138.3 VHN to 285.1 VHN, accompanied by a reduction in indentation diameter from 0.658 mm to 0.317 mm. Static simulation using SolidWorks showed a maximum von Mises stress of 0.05928 MPa, significantly below the AISI 1045 yield strength of 530 MPa. The maximum displacement was recorded at 1.16×10⁻⁵ mm, with a Factor of Safety (FoS) of 8,940.2, indicating that the material is highly safe for use. Functional testing of the machine showed that increasing the rotational speed from 380 rpm to 1200 rpm significantly improved the working capacity from 503.3 kg/hour to 828.5 kg/hour, with shelling efficiency rising from 88.08% to 98.05%. Overall, this study provides a scientific basis for material selection and blade design development to enhance the performance and reliability of corn sheller machines in the agricultural sector.